The Length-Weight Relationship and Condition Factor of the Red Cornetfish, Fistularia petimba Lacepède, 1803 in the Southeastern Mediterranean Coast of Türkiye (İskenderun Bay) - Deniz Ergüden; Servet Ahmet Doğdu; Cemal Turan (Turkish Journal of Bioscience and Collections)
Objective: In fisheries biology, length-weight relationship data are commonly used and helpful for determining the weight of an individual fish of known total length or total weight from length-frequency distribution. The present investigation aims to estimate the length-weight relationships and Fulton’s condition factors from the southeastern Mediterranean coast of Türkiye. Materials and Methods: A total of 368 red cornetfish, Fistularia petimba Lacepède, 1803 (203 females and 165 males) specimens were collected from the İskenderun Bay (southeastern Mediterranean, Türkiye) within the fishing periods of April 2019 and March 2020, caught by commercial bottom trawler at 28-42 m depths. Fish samples were measured in total length (TL) to the nearest 0.1 cm, and the total weight was scaled to the nearest 0.01 g. Results: The total length ranged from 21.50-56.60 cm, and the weight ranged from 8.10- 94.04 g for Fistularia petimba. The length-weight relationship was found as the W = 0.00033 × L3.126 (r2 = 0.963) for both sexes. The value of b is slightly different than 3 and showed positive allometric growth. The condition factor was found to be 0.539 for females, 0.526 for males, and 0.520 for both sexes. Conclusion: This study is the first investigation of the length-weight relationship and condition factor for Fistularia petimba from İskenderun Bay. The present study provides the basic fisheries parameters for this species in the Mediterranean Sea, which will be useful for fisheries management and fish population dynamics.